Manajemen Laba dalam Persepsi Etis Akuntan di Jawa Timur - Lontoh, Frederich Oscar; Lindrawati, . (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
The result of this research shows that the perception among accountants of all groups considering the earnings management ct don't have any significant difference. Only two of that s*factor was had any influence to the perception of the accountants considering the manajemen laba act. Consistency to GAAP and materiality is the only factors that shows some significant influence.